This is one of the example from the book named Higher Engg. Mathematics III by Dr. Kachot

Obtain the fourier series for:

$\displaystyle f(x)=\frac{1}{4} (\pi-x)^2 ; 0\leq x \leq 2\pi \\=f(x+2\pi);otherwise$

Here the value of

$\displaystyle a_{0}=\frac{1}{\pi}\int_{0}^{2\pi} f(x)dx = \frac{1}{\pi}\int_{0}^{2\pi} \frac{(\pi-x)^2}{4}dx = \frac{1}{4\pi}[-\frac{(\pi-x)^3}{3}]_{0}^{2\pi}$

Please explain the above step. Didn't get which integration formula the author applied. Also the minus sign is bugging me. Where did it come from?